Aspekty jawności prawa - Jabłońska-Bonca, Jolanta; Zieliński, Maciej (Wydział Prawa i Administracji UAM, 1988)
The problem of openness of law may be considered in many aspects, especially theoretical, formal, factual, ideological, axiological (including ethical), historal and comparative. The article is concerned with the problems of openness of law from a theoretical- legal point of view, with the attention focused on openness in creating the law, openness of legal norms (composed of openness with respect to information about the promulgation of a legal text and openness with respect to the contents of that information) and openness of enforcing the law. The article undertakes an attempt to show basic forms of openness of law, the degree of their universality, and the scopes and conditions of its implementation. The authors refer subsidiarily to some heuristic and justifying values of statements formulated in connection with other approaches to the analysed phenomenon. They refer most widely to a formal-legal aspect of openness, centering their attention on openness of Polish domestic statutory law.
Aspects of openness of law